The effect of public reporting of acute myocardial infarction on the choice of hospital - Mira Kim; Kyungshin Lee; Kyunghee Chae; Chai-Young Jung; Sangmin Lee; Hude Quan; Sukil Kim (PLoS ONE, 2025)
This study is to investigate the effect of public reporting of acute myocardial infarction (AMI) care on the people’s choice of hospitals. A cross-sectional study was conducted using an online questionnaire. The survey questions include the awareness and usage of public reporting, and the impact of the public reporting on the choice of hospitals. The difference in responses before and after acquiring information about public reporting was compared using multinomial logistic regression. Following a thorough validity check, 740 respondents are included in the final survey data set. The average age of respondents was 38.7 years (SD: 11.8), with 75.3% being female. Age distribution was as follows: 26.3% in their 20s, 23.5% in their 30s, 30.0% in their 40s, and 20.2% in their 50s. Most participants (73.7%) lived in metropolitan areas, and 75.1% had a university degree or higher. Before providing information about public reporting of AMI care, 62.8% of respondents selected ‘nearby hospitals’ as the best option for AMI patients, followed by ‘famous hospitals’, ‘usual hospital’, and ‘hospitals with good rates’. Non-health-related occupation shows significantly changed results of hospital choice between before and after obtaining public reporting information (p < 0.001). Publicly available hospital quality ratings can influence people’s choice of hospital and increase the risk of selecting a hospital with a good rating than the nearest hospital which is recommended for AMI patients. Policy-makers need to stress the importance of choosing the nearest hospital when AMI symptoms occur in addition to hospital ratings in the public reporting.